Antimicrobial Activity of a Cationic Guanidine Compound against Two Pathogenic Oral Bacteria - E. Escamilla-García; A. G. Alcázar-Pizaña; J. C. Segoviano-Ramírez; C. Del Angel-Mosqueda; A. P. López-Lozano; E. Cárdenas-Estrada; M. A. De La Garza-Ramos; C. E. Medina-De La Garza; M. Márquez (International Journal of Microbiology)
This study evaluated the potential antimicrobial properties of a polyguanidine (CatDex) on two oral bacteria. Chlorhexidine gluconate 1340 μmoL L−1 (CHX 0.12%) was used as control. Streptococcus mutans (S. mutans) and Porphyromonas gingivalis (P. gingivalis) were grown in BHI media. Bacterial sensitivity and antimicrobial activity were determined by the minimum inhibitory concentration (MIC) and Kirby-Bauer methods. To study side effects, that is, toxicity, dental pulp stem cells (DPSCs) were used. Fluorometric cytotoxicity and confocal microscopy assays were used in order to test cell viability. CatDex inhibited growth of S. mutans at all concentrations and growth of P. gingivalis at all concentrations except 25 μmoL L−1. The MIC of CatDex was 50 μmoL L−1 for both S. mutans and P. gingivalis. The inhibition of bacteria exposed for 8 h at 50 μmoL L−1 of CatDex exhibited increased antimicrobial activity over time, with 91% inhibition in both bacteria. The antimicrobial activities of CatDex and CHX were similar when tested on two common bacteria. CatDex was significantly less toxic to DPSCs. CatDex toxicity depended on time and not on concentration. With regard to clinical relevance, CatDex may have potential as a novel antimicrobial agent. Further studies are in progress.